GENDER STUDIES IN LINGUISTICS AND THEIR APPLICATION IN ENGLISH LANGUAGE TEACHING - Surmilova , Elena (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article explores the intersection of gender studies and linguistics in the context of English Language Teaching (ELT). Drawing on existing literature, the article examines the ways in which gender plays a role in language use and acquisition. It then explores the application of gender studies to ELT, considering strategies for promoting gender-inclusive language use and ways in which gender can be integrated into language teaching materials.